Evaluasi Keterampilan Menulis Makalah Pada Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar - Muhammad Syazali; I Ketut Widiade; Nursaptini Nursaptini; Ni Luh Putu Nina S; Hasnawati Hasnawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This study aims to evaluate the writing paper skills of students majoring in Elementary School teacher education study program. The research method used descriptive quantitative. The population of this study was 90 groups of students who programmed the Learning Outcomes Evaluation course. The sample consisted of 10 groups of students selected by purposive sampling based on the theme of their papers. The data were collected from the papers they compiled. Aspects that were evaluated are the systematics, introduction, discussion, conclusions, and references used. Additional data collected were the students’ assessment data on other group papers. The results of the analysis show that the degree of mastery of students in compiling papers was in a sufficient category. The ability to assess papers was still low. The difficulty lied in conformity to the template, writing the background, using sources, and presenting data in the form of tables or figures. All of these aspects were categorized as very low. This information can be used as a reference in developing a lecture system that can facilitate students to develop their skills in compiling papers.